Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1080/15299732.2010.496141
|View full text |Cite
|
Sign up to set email alerts
|

Women at War: Implications for Mental Health

Abstract: Few studies have investigated the impact of deployment stressors on the mental health outcomes of women deployed to Iraq in support of Operation Iraqi Freedom. This pilot study examined exposure to combat experiences and military sexual harassment in a sample of 54 active duty women and assessed the impact of these stressors on post-deployment posttraumatic stress disorder (PTSD) symptoms and depressive symptoms. Within 3 months of returning from deployment to Iraq, participants completed (a) the Combat Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 22 publications
5
37
0
Order By: Relevance
“…For women who were single and or had young children, this planning stage seemed especially stressful. Other studies have found similar results; for example, Dutra et al (2012) found that single military women struggle more with the separation process than married women. An estimated 9% of the National Guard parents are single and many have young children (ODUS, 2012).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…For women who were single and or had young children, this planning stage seemed especially stressful. Other studies have found similar results; for example, Dutra et al (2012) found that single military women struggle more with the separation process than married women. An estimated 9% of the National Guard parents are single and many have young children (ODUS, 2012).…”
Section: Discussionsupporting
confidence: 62%
“…The pre-and postdeployment processes might be especially challenging for single mothers, a growing segment of today's National Guard and Reserves members (ODUS, 2012). Dutra et al (2012) reported that single military mothers who must leave their children with grandparents or other family members have a particularly difficult time with the separation. Kelley et al (1994) found that single mothers, who were anticipating deployment in the navy, reported more separation anxiety and less family cohesiveness, commitment, and support than did married mothers.…”
mentioning
confidence: 98%
“…As many as 74% of US Servicewomen deployed to Iraq had one or more combat experiences, such as firing a weapon at the enemy or receiving incoming fire (Dutra et al, 2010). The wars in Iraq and Afghanistan in particular show how asymmetric warfare and the use of Improvised Explosive Devices (IEDs) and drone attacks have altered conceptions of the modern battlefield by blurring the definitions of 'the frontline'.…”
Section: Deployment Lengthmentioning
confidence: 99%
“…Dutra et al [20] found that lesbian, gay, bisexual or transgendered (LGBT) soldiers have developed PTSD and other health issues (such as depression, anxiety) from harassment from fellow soldiers due to their sexual orientation. Data on convictions do not exist because hate crimes on military bases often go unreported [21].…”
Section: Endogenous and Exogenous Factorsmentioning
confidence: 99%